2020
DOI: 10.1007/s10557-020-07019-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Endothelial Cell Function by Nucleic Acid Methylation in Cardiac Homeostasis and Disease

Abstract: Pathological remodelling of the myocardium, including inflammation, fibrosis and hypertrophy, in response to acute or chronic injury is central in the development and progression of heart failure (HF). While both resident and infiltrating cardiac cells are implicated in these pathophysiological processes, recent evidence has suggested that endothelial cells (ECs) may be the principal cell type responsible for orchestrating pathological changes in the failing heart. Epigenetic modification of nucleic acids, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 207 publications
(287 reference statements)
0
8
0
Order By: Relevance
“…Current advancements in epigenetic research, including epitranscriptomic regulation, suggested its role in regulating cardiovascular functions and kindled the hopes for effective RNA-based therapeutics to manage CVD ( 14 , 15 ). Recent studies have improved our understanding of N 6 -methyladenosine (m 6 A) mRNA methylation and its functional importance in RNA stability, translation efficiency, splicing, processing and degradation ( 16 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current advancements in epigenetic research, including epitranscriptomic regulation, suggested its role in regulating cardiovascular functions and kindled the hopes for effective RNA-based therapeutics to manage CVD ( 14 , 15 ). Recent studies have improved our understanding of N 6 -methyladenosine (m 6 A) mRNA methylation and its functional importance in RNA stability, translation efficiency, splicing, processing and degradation ( 16 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have linked DNA methylation with heart failure (HF) [50][51][52] . EC dysfunction is a critical mechanism in HF pathogenesis 53,54 . Current published data on DNA methylation modifications in septic patients have been predominantly examined in mixed populations of circulating cells 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the overexpression of m6A RNA methylase METTL3 plays an important role in increasing the levels of mitogen activated protein (MAP) 3K6, MAP4K5 and MAPK14, which leads to cardiomyocyte hypertrophy (62,63). In vitro experiments confirmed that inhibition of METTL3 could effectively block cardiomyocyte hypertrophy (73)(74)(75). Nearly a quarter of transcripts in human heart are related to m6A methylation, and FTO gene knockout can lead to impaired cardiac function (76).…”
Section: M6a Methylation and Calcium Homeostasismentioning
confidence: 99%
“…Endothelial cells are the main cell type involved in coordinating the pathological changes of heart failure, and their surface is often the direct place of a variety of inflammatory reactions (75). During the occurrence and development of heart failure, chronic inflammatory reaction can continuously promote the abnormal changes of myocardial structure and function (71,77).…”
Section: M6a Methylation and Inflammatory Responsementioning
confidence: 99%